2021
DOI: 10.1002/solr.202000816
|View full text |Cite
|
Sign up to set email alerts
|

Isomer‐Dependent Photovoltaic Properties of the [6,6]‐Phenyl‐C61 (or C71)‐Butyric Acid Methyl Esters

Abstract: Isomerism is common in fullerene derivatives, and the isomer‐dependent photovoltaic performance of fullerene derivatives is envisaged recently. This review article outlines recent progresses on isomerism of [6,6]‐phenyl‐C61 (or C71)‐butyric acid methyl esters (PCBMs), one of the most prevalent electronic acceptors in organic or perovskite solar cells. Recent developments about the effects of PCBMs isomers on the photovoltaic performance and device stability of organic or perovskite solar cells are summarized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Nevertheless, in case of the mixed solvent processed PCBM film, the surface coverage is comparatively better (as observed from SEM and AFM micrographs), and based on the significant increase in steady-state PL quenching and efficient charge extraction from TRPL data, it can be concluded that simply increasing the concentration of the solvent with lower vapor pressure up to an optimized ratio benefits the penetration of PCBM within the perovskite voids and helps in defect passivation, which may lead to enhanced interfacial interaction and better charge extraction and transport. 25,60 The J−V characteristics and detailed photoelectric parameters of PSCs fabricated from different solvent processing of the PCBM in PSCs are shown in Figure 4c and Table 1. For CB 1.0 −DCB 0 , CB 0.75 −DCB 0.25 , CB 0.5 −DCB 0.5 , and CB 0 − DCB 1.0 as solvents processed PCBM, the PCEs for champion devices are 17.72, 17.77, 18.46, and 17.57%, respectively, whereas Figure S8 depicts the statistical distribution of PCEs in 22 devices.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Nevertheless, in case of the mixed solvent processed PCBM film, the surface coverage is comparatively better (as observed from SEM and AFM micrographs), and based on the significant increase in steady-state PL quenching and efficient charge extraction from TRPL data, it can be concluded that simply increasing the concentration of the solvent with lower vapor pressure up to an optimized ratio benefits the penetration of PCBM within the perovskite voids and helps in defect passivation, which may lead to enhanced interfacial interaction and better charge extraction and transport. 25,60 The J−V characteristics and detailed photoelectric parameters of PSCs fabricated from different solvent processing of the PCBM in PSCs are shown in Figure 4c and Table 1. For CB 1.0 −DCB 0 , CB 0.75 −DCB 0.25 , CB 0.5 −DCB 0.5 , and CB 0 − DCB 1.0 as solvents processed PCBM, the PCEs for champion devices are 17.72, 17.77, 18.46, and 17.57%, respectively, whereas Figure S8 depicts the statistical distribution of PCEs in 22 devices.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Functionalized [70]fullerene ETMs have been seldom applied to inverted structure PSCs due to their changeable formulations in mixed form as well as their high cost in synthesis, separation, and purification [15b,98] . Therefore, one needs to strike a balance between targeted functionalization and isomerization control of C 70 derivatives.…”
Section: Functionalized Fullerenes For the Inverted Structure Pscsmentioning
confidence: 99%
“…Â 250 mm, toluene : hexane 1 : 1, 1 mL min À1 ): 4.9; UV (l max , nm): 306, 368, 428, 450. 1 H NMR (CDCl 3 ,d H , ppm): 7.84 (m, 2H, Ar), 7.19 (m, 2H, Ar), 7.03 (m, 2H, Ar), 6.79 (m, 2H, Ar), 3.82 (s, 3H; OCH 3 ), 3.72 (s, 3H; OCH 3 ); 19 F NMR (CDCl 3 , Àd F , ppm, J, Hz): 61.57 (m, 6F, CF 3 ), 61.91 (m, 12F, CF 3 ), 66.57 (q, 6F, J FF = 15.6 Hz, CF 3 ); APPI-MS (m/z (I,%)): 1618 (100%, C 70 (CF 3 ) 8 DPM À ).…”
Section: Synthetic Proceduresmentioning
confidence: 99%
“…They include the widely known n-type organic semiconducting materials PC[60]BM and PC[70]BM. 1 Methanofullerenes can be obtained by means of either [2+1] cycloaddition of carbenes or nucleophilic addition–substitution aka Bingel–Hirsch reaction. 2,3 Typically, a cyclopropane ring forms upon attachment to a common edge of two hexagons, i.e.…”
Section: Introductionmentioning
confidence: 99%